SISTEM PAKAR DIAGNOSIS PENYAKIT PADA TANAMAN VANILI MENGGUNAKAN METODE DEMPSTER-SHAFER BERBASIS WEB - ., Nanda; Hermanto, Bambang; Sudirman, Albertus (Universitas Lampung, 2020)
Vanilla (Vanilla planifolia Andrews) is an industrial plant that has high economic value as a foreign exchange-producing export commodity that is still potential to be developed in Indonesia. Vanilla is widely used in Indonesia as an auxiliary material for the food industry and in fragrance medicine. However, the high demand for vanilla is not balanced with an adequate level of productivity due to several obstacles in the development of vanilla in Indonesia. The main cause of obstacles in vanilla cultivation in Indonesia is the lack of understanding of vanilla farmers regarding diseases that attack vanilla plants. Therefore in this study an expert system was built that could diagnose vanilla plant diseases based on knowledge obtained from the experts directly. Expert system is built based on the web using the PHP programming language and Mysql database. The inference method used is the Dempster-shafer method. In this study consisted of 5 diseases and 16 symptomsÂ data. Test results show that: (1) Expertise testing by comparing the results of expert diagnoses and the system is appropriate and runs very well with a total average accuracy of 99.50% (2) External testing using a questionnaire involving 20 respondents namely